Sexually Dimorphic Scale Worms (Annelida: Polynoidae) From Hydrothermal Vents in the Okinawa Trough: Two New Species and Two New Sex Morphs - Zhang, Yanjie; Chen, Chong; Qiu, Jian-Wen (Frontiers in Marine Science, 2018)
Scale worms in the family Polynoidae are common inhabitants of both shallow-water and deep-sea ecosystems, but their diversity in the deep-sea remains poorly known. In the Western Pacific, only ten polynoid species have been described from deep-sea chemosynthetic ecosystems including hydrothermal vents and methane seeps. Here, we describe two new species of polynoids based on specimens collected from hydrothermal vents in the Okinawa Trough. Levensteiniella undomarginata sp. nov. is distinguished from other congeners by having elytra with a wave-shaped edge, and that males possess two pairs of nephridial papillae. Branchinotogluma elytropapillata sp. nov. differs from other congeners by having papillae on the elytral edge, and by males having a single pair of nephridial papillae and five pairs of C-shaped lamellae. Furthermore, we redescribe two known species, Lepidonotopodium okinawae Sui & Li, 2017 and Branchipolynoe pettiboneae Miura & Hashimota, 1991, for which morphological details were not provided in the original descriptions for males of the former species and females of the latter species. Sequencing of the cytochrome oxidase I (COI) gene in these four species confirmed the sexual dimorphism in vent polynoids for the first time, and provided reliable barcoding sequences for identifying these polychaetes.